2002
DOI: 10.1111/j.1530-0277.2002.tb02479.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ethanol Administration and Acute Allopregnanolone Administration Impair Spatial Memory in the Morris Water Task

Abstract: Acute ethanol administration and acute allopregnanolone administration impaired spatial memory performance but did not impair nonspatial memory performance in the Morris water task. These results demonstrate that both ethanol and allopregnanolone produce selective cognitive deficits that are not due to general sensory or motor deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 51 publications
3
35
2
Order By: Relevance
“…The work of multiple laboratories has produced a large body of evidence that suggests that ethanol-induced elevations of GABAergic neurosteroids contribute to several behavioral effects of ethanol, including ethanol’s memory-impairing effect (Kumar et al, 2009; Matthews et al, 2002; Morrow et al, 2001). Sanna et al (2004) have shown that in the hippocampal slice ethanol-induced de novo synthesis of the neurosteroid 3α,5α-THP mediates some of the ethanol enhancement of miniature and evoked IPSC amplitude that has been reported in CA1 neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The work of multiple laboratories has produced a large body of evidence that suggests that ethanol-induced elevations of GABAergic neurosteroids contribute to several behavioral effects of ethanol, including ethanol’s memory-impairing effect (Kumar et al, 2009; Matthews et al, 2002; Morrow et al, 2001). Sanna et al (2004) have shown that in the hippocampal slice ethanol-induced de novo synthesis of the neurosteroid 3α,5α-THP mediates some of the ethanol enhancement of miniature and evoked IPSC amplitude that has been reported in CA1 neurons.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of evidence from multiple laboratories suggests that ethanol-induced elevations of GABAergic neuroactive steroids contribute to several behavioral effects of ethanol in rodents. Neuroactive steroids have been shown to modulate ethanol’s anticonvulsant effects (VanDoren et al 2000), sedation (Khisti et al 2003), impairment of spatial memory (Matthews et al 2002; Morrow et al 2001), anxiolytic-like (Hirani et al 2005), antidepressant-like (Hirani et al 2002), and pro-aggressive (Fish et al 2001) actions. Most of these behavioral responses are prevented by pretreatment with finasteride and/or by prior adrenalectomy (Hirani et al 2002; 2005; VanDoren et al 2000).…”
Section: Acute Effects Of Ethanol On Gabaa Receptorsmentioning
confidence: 99%
“…Benzodiazepine tranquilizers are amnestic (Veselis et al, 2009), as are certain anesthetics such as propofol (Veselis et al, 2009) and isoflurane (Saab et al, 2010). Both alcohol and the neurosteroid THP impair spatial learning on the Morris Water Maze (Matthews et al, 2002). In adult CA1 hippocampus, α5β3γ2 GABARs have high expression extrasynaptically where they localize to the dendritic shaft and to the base of the dendritic spine (Brunig et al, 2002).…”
Section: Positive Modulators Of Gabaa Receptors and Synaptic Plasticitymentioning
confidence: 99%